The culture of sandals in Malaysia design and practicality / Fatin Nur Aainna Zahed - Zahed, Fatin Nur Aainna (2015)
The following report is an overall review study case of the Malaysian culture of wearing sandals. The purpose of this research is to examine and analyze the habit of sandals usage, the practicality of wearing sandals and the development of sandals in Malaysia. Sandals are widely used around the world as an everyday shoe because it is comfortable and lets you walk freely. Now, sandals have become a fashion trend as it has varities of patterns and colours to choose from.